The effect of graphene content on the structure and conductivity of cellulose/graphene composite - Farzana Abd Hamid,; Fauzani Md Salleh,; Nor Sabirin Mohamed,; Syed Bahari Ramadzan Syed Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The effect of graphene content on the structure and conductivity of an eco-friendly cellulose/ graphene (CG) composite was investigated. Different compositions of graphene content from 0 to 70 wt. % were prepared using the sol-gel method. Ionic liquids 1-butyl-3-methyl-imidazolium chloride was used to disperse graphene between the cellulose. The investigation showed that CG composite with higher graphene composition exhibits higher conductivity. The highest conductivity (2.85×10-4 S cm-1) was observed at 60 wt. % graphene composition. Sample without graphene showed the lowest conductivity of 1.77×10-7 S cm-1, which acts as an insulator. The high conductivity of CG composite can be associated with the X-ray diffraction (XRD) patterns. The XRD patterns of α-cellulose exhibits a decrease in crystallinity at peak 15° and 22° due to the depolymerization in CG composite. At 60 wt. % composition, XRD pattern showed the decrease in intensity at peak 26° indicates that graphene is more dispersed in the cellulose mixture. This is supported by Fourier transform infrared spectrum of CG composite where the absorption peaks of C-O stretching are weakened at wavelength of 1163 and 1032 cm-1, suggested dehydration and rupture of cellulose. The dehydration and rupture of cellulose result in the high conductivity of CG composite. This research is believed to provide an eco-friendly method to produce cellulose/graphene composite which is useful in future applications of energy.